VARIABILITY OF Colletotrichum lindemuthianum IN COMMON BEAN IN WESTERN PARANÁ - BONETT, Lucimar Pereira; SCHEWE, Ivânia; SILVA, Luciano Ivano da (Scientia Agraria, 2008)
The great pathogen variability of the fungus Colletotrichum lindemuthianum and its widespread distribution across several common bean regions in Brazil, particularly in the southern and southeastern regions, is causing serious problems for producers as well as breeders. The purpose of this paper was the identification of Colletotrichum lindemuthianum races in common bean fields in the western part of Paraná state, one of the leaders in the Brazilian production. Anthracnose-infected pods were collected and the surface disinfected with sodium hypochlorite. Lesion fragments were transferred to PDA medium containing streptomycin and incubated for eight days at 28 ºC. For selection of the isolates the mycelium of the fungus were seeded two or three times on Petri dishes with the same medium. After incubation a spore solution was obtained by the dilution method, adjusted to a concentration of 1.2 x 106 spores mL-1. The suspension was applied on the first trifoliote leaf of the 12 differentiating cultivars. The symptoms were evaluated after 10 days, on a 1 to 9 scale. Among the 61 evaluated isolates, the races 52, 65, 81, 83, 321, and 337 were identified. The races 52, 83 and 337 were observed for the first time in common bean fields in western Paraná that demonstrates increase in the variability of the pathogen in the region and the need of a periodic monitoring.